Investigation of neonicotinoid pesticides in Slovenian honey by LC-MS/MS. (May 2019) - Mrzlikar, Miha; Heath, David; Heath, Ester; Markelj, Jernej; Kandolf Borovšak, Andreja; Prosen, Helena
Abstract: A considerable evidence links neonicotinoids and colony collapse disorder in bees. In 2011, Slovenia imposed a moratorium on three neonicotinoids, but there has been no country-wide study on its effectiveness. Using honey is a non-invasive way of checking the exposure of bees to neonicotinoids. In this study, a reliable analytical method for five neonicotinoids in honey was developed, using two extraction techniques (SPE, QuEChERS) and LC-MS/MS (SRM). Validation and calculation of expanded uncertainty was performed at 10 and 50 ng/g. Both methods gave satisfactory recoveries (68.2–113.6%), precision (0.9–8.0%), and low LODs (0.05–0.97 ng/g). QuEChERS had lower uncertainty, better accuracy, and lower matrix effect, and was applied to the analysis of 51 honey samples from Slovenia (2014–2016). Low contamination of acetamiprid and thiacloprid was found. This survey is an important contribution to the worldwide database of honey contamination with neonicotinoids and the threat they pose to the honeybees. Highlights: Assessment of the effectiveness of the current ban on neonicotinoids in Slovenia. Important contribution to the worldwide database of neonicotinoid contamination. First study with full validation of QuEChERS and SPE for neonicotinoids in honey. Compared validation parameters and uncertainties of determination with LC-MS/MS. Special emphasis on matrix removal and matrix effects with LC-MS/MS.